The Effect of Emotional Intelligence on Knowledge Sharing with Trust as a Moderator Variable: The Case of Distro Employees in Citarum Village Bandung - Lisha Adzanta Firmansyah; Sri Raharso; Tjahjawati, Sri Surjani (Quantitative Economics and Management Studies, 2025)
This research investigates the impact of emotional intelligence on knowledge sharing behavior, with trust serving as a moderating variable, within distro businesses located in the Citarum Subdistrict of Bandung. Operating within the creative economy sector, these businesses encounter intense competition from both domestic and international markets. To maintain their sustainability, it is crucial to enhance emotional intelligence, encourage knowledge-sharing activities, and establish trust among employees. Employing a quantitative approach through surveys, the study gathered data from 179 distro employees. Questionnaires were used as the primary data collection tool, and the data were analyzed using regression techniques. The findings reveal that emotional intelligence has a positive influence on knowledge sharing, and that trust significantly strengthens this relationship by amplifying the effect of emotional intelligence. These results highlight the vital role of trust in creative work settings and offer practical recommendations for distro business stakeholders to foster a collaborative work culture grounded in emotional intelligence and mutual trust.